Body Scanners at Airports: The Dilemma between Aviation Security and Passenger Privacy Rights - Wulandari, Mentari Putri; Ardianto, Budi; Yin, Tan Xuan (Faculty of Law, Universitas Jambi, 2025)
The aviation industry has tightened its security measures due to the increasing threat of attacks at airports. The use of body scanners can be considered an important step in enhancing flight security by detecting prohibited items carried by passengers. However, this can raise privacy concerns, as it may reveal sensitive information about the passengers' bodies. Although security checks at airports are often seen as an extension of aviation security, the implementation and practices of these checks must adhere to human rights and individual privacy. Therefore, the Chicago Convention of 1944 safeguards the safety of international civil aviation and protects the rights of passengers. Although the use of body scanners can be seen as a security measure, it must be carefully considered to balance the need for safety with the protection of individual privacy. This article aims to explain the implications of body scanners on the privacy rights of airline passengers. This research employs normative legal research, and the research method applied in this study is a literature review utilizing books, scientific journals, and other sources that regulate body scanners and passenger privacy rights at airports.